Small-Cell Lung Cancer with Positive Anti-NMDAR and Anti-AMPAR Antibodies Paraneoplastic Limbic Encephalitis - Sabina Boangher; Pascal Mespouille; Corina-Mihaela Filip; Sophie Goffette (Case Reports in Neurological Medicine)
We report the case of a 66-year-old woman, with paraneoplastic limbic encephalitis, treated 6 months earlier for bladder neoplasia. The patient presented to the emergency room with rapidly increasing symptoms, noninfectious cerebral spinal fluid associated with positive anti-NMDAR (as well as in serum) and positive AMPAR antibodies in the serum. Four months later, the patient was diagnosed with a small-cell lung cancer for which chemotherapy and radiotherapy was commenced. Simultaneously, endoscopic surgical treatment was undertaken for an in situ relapse of the bladder neoplasm. After the completion of 3 cycles of chemotherapy her neurological status temporarily worsened. The cerebral MRI did not show signs of encephalitis such as increased T2/FLAIR signal intensity in the mesial temporal lobes and limbic systems. No specific treatment was prescribed. Limbic encephalitis can be associated with malignant tumors such as lung carcinoma. Several cases reported in the literature have shown cognitive improvement after tumoral therapy. Regarding our experience, significant progress was achieved through immuno-modulatory treatment. A transitory deterioration of the cognitive process was perceived during the chemotherapy sessions.